The Effect of ChatGPT Usage on Student Learning Motivation at STIE Pancasetia Banjarmasin - Nico Kosasih (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of the use of artificial intelligence technology, specifically ChatGPT, on the learning motivation of STIE Pancasetia Banjarmasin students in the Change Management course. ChatGPT is an AI-based language model that provides fast, flexible, and interactive access to information, and has the potential to increase learning effectiveness. The method used is a quantitative approach with a questionnaire data collection technique for 40 students. The results of the regression analysis show that the use of ChatGPT has a significant effect on student learning motivation, with a significance value of 0.014 (<0.05). The coefficient of determination of 0.150 indicates that 15% of the variation in learning motivation can be explained by the use of ChatGPT, while the remaining 85% is influenced by other factors. These findings emphasize the importance of using ChatGPT wisely as a learning tool that can support student learning motivation in the digital era.